Oral Health Literacy among Public University Undergraduate Students and Associated Factors - Jaafar , A; Al-Kadhim, AHA; Ab Malik, N (IIUM Medical Journal Malaysia, 2020)
Introduction: Oral health literacy is an essential element of an individual to make better oral health decision. Low oral health literacy (OHL) is associated with poor oral health decision and outcome. This study aimed to determine factors associated with oral health literacy among undergraduate students in one of the public universities of Malaysia. Materials and methods: This is a cross-sectional study which was undertaken among the undergraduate students of Universiti Sains Islam Malaysia (USIM). Sample selection was done randomly. A validated oral health literacy index of Malay version was used throughout the study. Ethical approval was obtained from the University Research Ethics Committee and respondents had given their consent prior to the data collection. Data analysis was performed using IBM SPSS software version 24.0 and the significant level was set at p< 0.05. Results: The mean oral health literacy of the university undergraduate students was 77.7 (95% CI= 76.75, 78.71). Multiple linear regression indicated that female has higher OHL (β= 4.19; 95% CI= 1.99, 6.39; p< 0.001), social science stream has lower OHL (β= -9.14; 95% CI= - 11.20, -7.07; p< 0.001) and higher education level of father had higher OHL (β= 1.97; 95% CI= 0.10, 3.83; p= 0.039) than their counterparts. Conclusion: Oral health literacy is higher among the science streams students compared to the social sciences streams. This suggests that science education might play a significant role in health literacy and improving health outcomes.